Point Cloud Merging for Complete 3D Surface Reconstruction - Matiukas, V.; Miniotas, D. (Elektronika ir Elektrotechnika, 2011)
This article addresses the problem of reconstructing 3D surfaces from unorganized point sets (also known as point clouds). Thisissue is common to many different areas of science and engineering, including computer graphics and computer vision. Unorganizedpoint sets can be acquired in different ways, e.g., using laser scanners, computer tomography, magnetic resonance imaging, multicameravision systems, etc. This paper presents a method for point cloud merging that allows calculating the initial rotation andtranslation between point clouds of different viewing angles. By tracking the marker’s position, scanning and point cloud registrationcan be done in real time and with high accuracy. Ill. 7, bibl. 11 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.616